Don't sleep with the dead - Vo, Nghi (Tordotcom, 2025)
"Nick Carraway--paper soldier and novelist--has found a life and a living watching the mad magical spectacle of New York high society in the late thirties. He's good at watching, and he's even better at pretending: pretending to be straight, pretending to be human, pretending he's forgotten the events of that summer in 1922. On the eve of the second World War, however, Nick learns that someone's been watching him pretend and that memory goes both ways. When he sees a familiar face one very dark night, it quickly becomes clear that dead or not, damned or not, Jay Gatsby isn't done with him. In all paper there is memory, and Nick's ghost has come home."--Provided by publisher.